ANALYSIS OF THE SURFACE LAYER FORMATION OF SINGLE-CYLINDER ENGINE COMBUSTION CHAMBER WITH PHOSPHOROUS-FREE AND CONVENTIONAL ENGINE LUBRICANTS - Yuksek, L.; Kaleli, H.; Ozkan, D. (SCIBULCOM LTD, 2014)
Phosphorus-free engine lubricants are gaining importance for preventing catalyst poisoning which is the major deactivation mechanism that causes the malfunction of 3-way catalysts. The main purpose of this paper is to evaluate the mechanism of surface layer formation on combustion chamber of spark ignition engines with phosphorous-free and phosphorous-containing engine lubricants. An experimental endurance test was conducted for 100 h at equal load conditions for each lubricant. Endurance tests were applied with a laboratory engine test bench. Subsequently, engines dismantled and cylinder liners were cut accurately to obtain specimens for microscopic examination. Optical microscopy, scanning electron microscopy and energy dispersive X-ray spectroscopy methods were used for evaluation. Elemental measurements on the surface which were obtained by X-ray spectroscopy were examined statistically. Results of the experiments showed that the phosphorous-containing lubricant deposited more carbon and oxygen although less manganese and silica than the phosphorous-containing rival. After the X-ray spectroscopy of the combustion chamber surface at top dead centre, iron element composition of the phosphorus-free lubricant was notably higher than phosphorus containing oil.
Keywords: phosphorous-free engine lubricant; combustion chamber; X-ray spectroscopy; additive layer formation; cylinder liner; WEAR; Engineering